Preventing religion as a legitimation of violence: Internalization of moderation values in Islamic religious education among junior high school students - Ru iya, Sutipyo; Pangisti, Qo idah Ariq; Yusutria, Yusutria; Niwae, Yahya; Masduki, Yusron (LPPM Universitas Ibn Khaldun, Bogor, 2025)
Violence in the name of religion often occurs around us. According to several research results, one of the reasons is the lack of knowledge about religious moderation. Moderate behavior in religion needs to be encouraged from an early age, especially in junior high school. Junior high school students are in an ambiguous stage of development, between childhood and adulthood, so they need to internalize good social and humanitarian values. This study aims to explore the process of internalizing the values of religious moderation in junior high schools carried out by Islamic Religious Education teachers. The method used is a qualitative method with a phenomenological approach. Data were collected through in-depth interviews, observation, and documentation. Data sources from Islamic Religious Education teachers, other religious teachers, Muslim students and students of religions other than Islam. The process carried out by Islamic Religious Education teachers includes three stages: pre-learning, reinforcement learning, and the internalization stage. Each stage is carried out carefully by Islamic Religious Education teachers supported by the entire school community. Through three stages of internalization of the values of religious moderation carried out in this school, the impact was that there was no violence in the name of religion carried out by students, teachers and education staff. The three stages of the process of internalizing the values of religious moderation carried out by Islamic Religious Education teachers are worthy of being adopted and duplicated in other places.